Study the People's Satisfaction in Community to Pig farming in Park-Ou District, Louangprabang Province - KHOMTHAVONG, Anousone; MANIVANH, Nouphone; NAOYENG, Khamkeo (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This experiment aims to study the problems and causes of pollution from pig farms as well as the effects of pollution caused by pig farms that affect the environment and people in the community by analyzing the water quality values ​​released from pig farms that include pH, EC, DO and water temperature, also studying people's satisfaction with pig farms in the community. By selecting 4 villages namely: Hatpang, Fay, Hatya and Xanghai Village, Pak U District, Luang Pra Bang Province. In collecting samples for analysis, samples were selected from sewage treatment in each farm, 9 farms from 3 parts from pig farms: PC farm, Betago Farm and People's Farm to measure the standard values ​​of water quality including pH, EC, DO and temperature. From the results of the analysis of the various values, it has been shown that all these 3 farms have different water quality values ​​and there is a statistical difference at p<0.05. In this, the most polluted water is untreated at Betako Farm. The value of DO at the level of 1.92 is the lowest value which cannot make aquatic animals live and cannot be used again because it reduces the standard value to 3 times and even more than that, the value of EC is only 41 us/cm, which is a value that indicates the lowest value of electrical induction and reduces the standard value to 200 us/cm, which means that the sewage treatment from Betako Farm is Non-standard and compared to other treatment, especially People's Farm treatment has a better standard treatment which is shown in various indicator values ​​such as the value of pH is 7.78, the value of Ec. (us/cm) is 397.66, the value of DO is 5.63, and the value of Temp (°C) is 29.05 and the following is PC farm. In addition, the results of the study conducted by interviewing a group of people in the community to the idea of ​​making a farm close to the community revealed that the people living in the area have a moderate level of interest with an average value of 3.10, which is expressed in each aspect such as: household and personnel management with a total average value of 3.76, characteristics of the pig farm with a total average value of 3.60, waste management that affects odor pollution. From the pig farm with an average value of 3.05, people per benefit from the farm with an average value of 2.15 respectively.